OA44 Increasing access to rehabilitation for knee and hip osteoarthritis - ESCAPE-pain in leisure/community centres. (23rd April 2022) - Hurley, Michael V; Carter, Andrea; Sheldon, Helen; Connolly, Margaret; ,
Abstract: Background/Aims: Enabling Self-management and Coping with Arthritic Pain using Exercise, ESCAPE-pain, is a rehabilitation programme for people with knee and/or hip osteoarthritis (OA) that reduces pain, improves function and reduces healthcare utilisation. The programme is usually delivered in physiotherapy departments. However, financial and logistical constraints in the NHS limit the number of people who can access the programme. Delivering ESCAPE-pain in community centres would increase accessibility, "reach" and provide better on-going support. We trained exercise professionals to deliver ESCAPE-pain in leisure/community centres, monitored whether it continued to be effective and gathered the experiences of participants, facilitators and organisations delivering the programme. Methods: 369 exercise professionals were trained to deliver ESCAPE-pain in 41 leisure and community centres across the UK. Pain, function and quality of life (using Knee or Hip Osteoarthritis Outcome Score, K/HOOS), and self-reported activity levels (minutes/week) were measured before and after the programme. Programme participant's and facilitator/organisation's experiences were evaluated using semi-structured interviews. Results: 1386 participants (998 female) were recruited, mean age 70 years. Before the programme only 24% of participants were "fairly/moderately active" (doing >30 mins activity/week), after the programme 78% were "fairly/moderately active (doing >150mins activity/week). These increased activity levels were maintained for 12 months after completing the programme. Participants enjoyed the programme and reported improvements in their pain (10 K/HOOS points; p < 0.0001), function (9pts; p < 0.0001), QoL (10pts; p < 0.0001), understanding, exercise self-efficacy (their confidence in using exercise to control pain and its impact), mental wellbeing and reduced reliance on healthcare professions, medication and surgery. They were able to walk better, farther, without an aid and returned to former activities, felt better in themselves and "the world was a brighter place". Most people were planning to continue exercising after completing the programme and had joined classes and taken up activities they enjoyed such as swimming, golf, walking, yoga. The exercise professionals enjoyed getting involved in healthcare interventions and offering people an effective intervention. The 17 partner organisations found the programme increased their portfolio of interventions, forming links with the healthcare sector that they saw as important in the future. Many organisations planned to expand the number of centres running the programme permanently. To create revenue streams that enabled them to sustain delivery of ESCAPE-pain organisations formed collaborations with clinical departments, contracted by CCGs, charged a nominal amount for the programme or membership for the organisation and are expanding the programme to other centres within their organisation. Conclusion: ESCAPE-pain can be safely delivered by exercise professionals in leisure/community centres, maintains its clinical effectiveness and nurtures habitual exercise. The community-based programme is capable of helping the large and rapidly increasing number of people with OA. ESCAPE-pain is now being delivered in leisure centres across the UK. Disclosure: M.V. Hurley: None. A. Carter: None. H. Sheldon: None. M. Connolly: None.